Truncated WT1 Protein Isoform Expression Is Increased in MCF-7 Cells with Long-Term Estrogen Depletion - Saavedra-Alonso Santiago; Zapata-Benavides Pablo; Mendoza-Gamboa Edgar; Chavez-Escamilla Ana Karina; Arellano-Rodríguez Mariela; Rodriguez-Padilla Cristina (International Journal of Breast Cancer)
Background. The wt1 gene codes for a transcription factor that presents several protein isoforms with diverse biological properties, capable of positively and negatively regulating genes involved in proliferation, differentiation, and apoptosis. WT1 protein is overexpressed in more than 90% of breast cancer; however, its role during tumor progression is still unknown. Methodology. In this work, we analyzed the expression of WT1 isoforms in several breast cancer cells with different tumor marker statuses and an in vitro assay using MCF-7 cells cultured with long-term estrogen depletion (MCF-7 LTED cells) with the finality to mimic the process of switching from hormone-dependent to hormone-independent. Moreover, growth kinetics, sensitivity to tamoxifen, and relative expression analysis of ER and Her2/neu were performed. Results. Initially, the expression of 52-54 kDa protein isoform of WT1 in the breast cancer cell line ER (+) was detected by western blot and was absent in ER (-), and the 36-38 kDa protein isoform of WT1 was detected in all cell lines analyzed. The analysis of alternative splicing by RT-PCR shows that the 17AA (+)/KTS (-) isoform of WT1 was the most frequent in the four cell lines analyzed. In vitro, the MCF-7 cells in the estrogen depletion assay show an increase in the expression of the 52-54 kDa isoform of WT1 in the first 48 hours, and this was maintained until week 13, and later, this expression was decreased, and the 36-38 kDa isoform of WT1 did not show change during the first 48 hours but from week 1 showed an increase of expression, and this remained until week 27. Growth kinetic analysis showed that MCF-7 LTED cells presented a 1.4-fold decrease in cellular proliferation compared to MCF-7 cells cultured under normal conditions. In addition, MCF-7 LTED cells showed a decrease in sensitivity to the antiproliferative effect of tamoxifen (p≤0.05). Samples collected until week 57 analyzed by qRT-PCR showed an increase in the relative expression of the Her2/neu and ER. Conclusions. Modulation of protein isoforms showed differential expression of WT1 isoforms dependent on estrogen receptor. The absence of 52-54 kDa and the presence of the 36-38 kDa protein isoform of WT1 were detected in ER-negative breast cancer cell lines classified as advanced stage cells. Long-term estrogen depletion assay in MCF-7 cells increased the expression of the 36-38 kDa isoform and reduced the 52-54 kDa isoform, and these cells show an increase in the expression of tumor markers of ER and Her2/neu. MCF-7 LTED cells showed low proliferation and insensitivity to tamoxifen compared to MCF-7 cells in normal conditions. These results support the theory about the relationship of the 36-38 kDa isoform of WT1 and the absence of ER function in advanced breast cancer.